Readiness to Change the Management System of the Regional General Hospital of North Buton Regency Towards Regional Public Service Agency - Fortanita, Wa Ode; Risky, Sartini; Rahmawati, Rahmawati (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: The transformation of North Buton Hospital into a Regional Public Service Agency faces significant challenges, particularly in human resources due to the dominance of contract labor, leading to personnel instability. Another major obstacle is the lack of understanding among policymakers about the impact of this transformation on Regional Original Revenue, which could delay the adoption of the model that is crucial for enhancing the efficiency, transparency, and quality of health services. These challenges are further compounded by operational and financial limitations, such as restricted flexibility in resource management, highlighting the urgent need for transformation. Method: This qualitative study, using a case study design, involved nine informants, including key hospital officials and staff. Data were collected through interviews, observations, and document reviews, and analyzed using the N-VIVO software. Result: The findings indicate that North Buton Hospital is substantively prepared for the transformation, with a solid financial strategy and a good understanding of regulations. Technically, the hospital has successfully compiled and verified essential documents, such as the Strategic Plan and Minimum Service Standards. Conclusion: The study concludes that while North Buton Hospital is generally ready to transition to Regional Public Service Agency status, overcoming these challenges is essential. Recommendations include increasing local government support, enhancing human resource training, and developing IT infrastructure for the Hospital Management Information System to ensure a successful transformation and improved public health services.